Pengaruh Desain Interior Kelas PAUD Terhadap Perkembangan Emosional (Rasa Empati) Anak Usia Dini Dalam Proses Pembelajaran di RA Nurbaiti Kota Padang - Desmariani, Evi; Jendriadi, Jendriadi; Yuniarti, Lisa (Indonesian Research Journal on Education, 2022)
The problem in this research is that when the learning process takes place, the emotional behavior reactions of children are very bad (negative), such as children who have not been able to control their emotional intelligence so that they are lazy to follow the activities given by the teacher, like to make noise, cry, lethargic, not enthusiastic, lack of concentration. , busy with their own activities, wrestling, likes to annoyfriends, likes to talk during learning, doze off, some even have not come to school for a few days with the excuse of being lazy and bored. For this reason, the author is interested in improving the interior design of the classroom through experimental research with a better and more conducive classroom interior design. The purpose of this study was to determine whether classroom interior design can develop negative emotionalintelligence into positive emotional intelligence at RA Nurbaiti, Padang City. The research used isquantitative in the form of a quasi-experimental. The population of this study were all children at RA Nurbaiti, Padang City, totaling 15 people, namely the Learning Group (Rombel) A. The experimental class was given the treatment of a class interior design that had been arranged while the control class did not do a class interior design. The data collection technique is in the form of an assessment instrument with 6 meetings. Based on data analysis, the average test result of the experimental group was 83.75 with a standard deviation of 11.5291 with a median of 87.500 while the control group averaged 74.17 with a deviation of 13.3446 and a median of 81.300. In testing the hypothesis obtained t count 2.102 and t table2.048 at the real level = 0.05. So it can be concluded that the interior arrangement of the classroom has an effect on the emotional intelligence of children aged 4-5 years at RA Nurbaiti, Padang City.